2023
DOI: 10.1186/s41072-023-00134-z
|View full text |Cite
|
Sign up to set email alerts
|

Market access and seaport efficiency: the case of container handling in Norway

Abstract: Comprehensive studies on the impact of market access on port efficiency are scarce, and the problem that market access indicators are potentially endogenous lacks treatment in maritime economics. This paper offers both theoretical and empirical advances to fill these research gaps. First, it pioneers in the use of Stochastic semi-Nonparametric Envelopment of Z variables Data for measuring port efficiency, and further develops the methodology for panel data and proposes an instrumental variable extension for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…In addition, recent studies further emphasize the role of connectivity and sustainability in port efficiency. Rødseth et al [39] stressed that the Liner Shipping Connectivity Index (LSCI) is vital for influencing port efficiency through improved market access. Li et al [40] demonstrated that sustainable practices, such as reducing carbon emissions, are crucial for enhancing port efficiency.…”
Section: Smart Port Efficiencymentioning
confidence: 99%
“…In addition, recent studies further emphasize the role of connectivity and sustainability in port efficiency. Rødseth et al [39] stressed that the Liner Shipping Connectivity Index (LSCI) is vital for influencing port efficiency through improved market access. Li et al [40] demonstrated that sustainable practices, such as reducing carbon emissions, are crucial for enhancing port efficiency.…”
Section: Smart Port Efficiencymentioning
confidence: 99%